2019
DOI: 10.1038/s41598-019-49700-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Genetic Engineering, Structural Variation, and Antimicrobial Resistance Markers in Bacterial Biothreat Pathogens by Nanopore Sequencing

Abstract: Widespread release of Bacillus anthracis (anthrax) or Yersinia pestis (plague) would prompt a public health emergency. During an exposure event, high-quality whole genome sequencing (WGS) can identify genetic engineering, including the introduction of antimicrobial resistance (AMR) genes. Here, we developed rapid WGS laboratory and bioinformatics workflows using a long-read nanopore sequencer (MinION) for Y. pestis (6.5 h) and B. anthracis (8.5 h) and sequenced strains with different AMR profiles. Both salt-pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Only 45 min of bioinformatics analysis (Pima version 01, https://github.com) using 120,000 basecalled nanopore reads was sufficient to assemble and confirm the absence of known AMR genes/markers associated with resistance to quinolones and tetracyclines ( Figure 1, panel B) (13). We detected no mutations in gyrA, gyrB, parC, or parE genes, identified no AMR genes contained in the Resfinder database (https://cge.…”
Section: The Studymentioning
confidence: 92%
See 4 more Smart Citations
“…Only 45 min of bioinformatics analysis (Pima version 01, https://github.com) using 120,000 basecalled nanopore reads was sufficient to assemble and confirm the absence of known AMR genes/markers associated with resistance to quinolones and tetracyclines ( Figure 1, panel B) (13). We detected no mutations in gyrA, gyrB, parC, or parE genes, identified no AMR genes contained in the Resfinder database (https://cge.…”
Section: The Studymentioning
confidence: 92%
“…Although genetic analysis is useful for detection of known AMR genes/markers in the B. anthracis genome, phenotypic susceptibility testing by BMD remains essential to detect functional resistance (7,13). By using the conventional BMD method, we found that strain Ba0914 was susceptible to ciprofloxacin, levofloxacin, tetracycline, doxycycline, penicillin, and amoxicillin.…”
Section: The Studymentioning
confidence: 99%
See 3 more Smart Citations